The Effect of Food Selectivity on Nutritional Adequacy for Autistic Children in Western Region, Saudi Arabia - Kasnawi, Fatema Ahmad; Jambi, Hanan Abdulsalam (Journal of medical and pharmaceutical sciences, 2020)
Objectives: To investigate the association of Food Selectivity domains: food refusal (FR), high-frequency single food intake (HFSFI), and limited food repertoire (LFR), restricted diets, and appetite-affecting medications with nutritional adequacy in autistic children aged 6-12 years in the Western region of Saudi Arabia (SA).Methods: thirty-two autistic children from six autistic centres participated in the study. Height and weight measured for each child and body mass index were calculated. Mothers of autistic children provided diet information by completing 3-day food records and a food frequency questionnaire.Results: only three children were taking appetite-affecting medications and two children were on a restricted diet. Most of the autistic children had an adequate intake of carbohydrate (87.5%), protein (93.8%), and fat (93.8%). However, the adequacy of fiber and micronutrients (iron, folate, calcium, zinc, vitamin A, vitamin D and vitamin E) appeared in less than 50% of autistic children, but vitamin C and vitamin B12 adequacy appeared in ≥ 50% of autistic children. The FR and LFR were not associated (P= 0.091 and P= 0.706 respectively) with nutritional adequacy. The HFSFI was significantly associated (P=0.021) with nutritional adequacy.Conclusion: Food Selectivity is a frequent problem in autistic children in the Western region in SA, which affects their nutritional adequacy. Therefore, in SA further studies are needed related nutrition with autism, to improve the nutritional status of autistic children.
Keywords: autistic children; Food Selectivity; nutritional adequacy